Sound location can influence audiovisual speech perception when spatial attention is manipulated. - Tiippana, K; Puharinen, H; Möttönen, R; Sams, M (2011)
Audiovisual speech perception has been considered to operate independent of sound location, since the McGurk effect (altered auditory speech perception caused by conflicting visual speech) has been shown to be unaffected by whether speech sounds are presented in the same or different location as a talking face. Here we show that sound location effects arise with manipulation of spatial attention. Sounds were presented from loudspeakers in five locations: the centre (location of the talking face) and 45°/90° to the left/right. Auditory spatial attention was focused on a location by presenting the majority (90%) of sounds from this location. In Experiment 1, the majority of sounds emanated from the centre, and the McGurk effect was enhanced there. In Experiment 2, the major location was 90° to the left, causing the McGurk effect to be stronger on the left and centre than on the right. Under control conditions, when sounds were presented with equal probability from all locations, the McGurk effect tended to be stronger for sounds emanating from the centre, but this tendency was not reliable. Additionally, reaction times were the shortest for a congruent audiovisual stimulus, and this was the case independent of location. Our main finding is that sound location can modulate audiovisual speech perception, and that spatial attention plays a role in this modulation.